HUBUNGAN PERSEPSI SISWA TENTANG KOMPETENSI PROFESIONAL GURU DENGAN HASIL BELAJAR KONSTRUKSI BANGUNAN SISWA KELAS X DI SMK NEGERI 1 BUKITTINGGI - 827-835 , Viro Dinda (CIVED, 2015)
ABSTRACT The aim of this research was to explain the correlation of students’ perception of professional teachers’ competence and students’ learning outcomes. In this research, the researcher used descriptive research by using correlational approach. The population of this research was the whole students of building construction students grade X of Vocational School 1 Bukittinggi in academic year 2014/2015. The total of the population was 107 students. The researcher took 84 students of 107 as the sample of the research that was taken by using proporsional random sampling. The data used in this research were primary and secondary data. The result of the research showed that there was a significant correlation of students’ perception of professional teachers’ competence and students’ learning outcomes. grade Sig (2-tailed) 0,000<Alpha (0,05). The result of the test emphasized that there was a significant correlation of students’ perception of professional teachers’ competence and students’ learning outcomes. Key words: perception, professional competence, learning outcomes